2020
DOI: 10.1074/jbc.ra120.012908
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of a novel repressor, SghR, controlling Agrobacterium infection by cross-talking to plants

Abstract: Agrobacterium tumefaciens infects various plants and causes crown gall diseases involving temporal expression of virulence factors. SghA is a newly-identified virulence factor enzymatically releasing salicylic acid from its glucoside conjugate and controlling the plant tumor development. Here we report the structural basis of SghR, a LacI-type transcription factor and highly conserved in Rhizobiaceae family, regulating the expression of SghA and involved in tumorigenesis. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Comparison of our structure with that of the DNA-bound Plasmodium falciparum transcription factor SIP2, which contains two AP2 domains [Protein Data Bank (PDB) ID: 6SY0], revealed that SIP2 uses an - turn, rather than the  sheet observed in AtWRI1, for specific DNA recognition that is quite common as indicated in our recently described SghR (salicylic acid -glucoside hydrolase repressor)-DNA structure (Fig. 3A) (42). The domain organization of SIP2 was also significantly different from that of AtWRI1, particularly in the domain linker region (Fig.…”
Section: Structural Comparison Of Atwri1 With Other Ap2 Domain-contai...mentioning
confidence: 66%
“…Comparison of our structure with that of the DNA-bound Plasmodium falciparum transcription factor SIP2, which contains two AP2 domains [Protein Data Bank (PDB) ID: 6SY0], revealed that SIP2 uses an - turn, rather than the  sheet observed in AtWRI1, for specific DNA recognition that is quite common as indicated in our recently described SghR (salicylic acid -glucoside hydrolase repressor)-DNA structure (Fig. 3A) (42). The domain organization of SIP2 was also significantly different from that of AtWRI1, particularly in the domain linker region (Fig.…”
Section: Structural Comparison Of Atwri1 With Other Ap2 Domain-contai...mentioning
confidence: 66%
“…Wang et al (131) recently found that A. tumefaciens can produce a SAG hydrolase, SghA, to hydrolyze SAG in order to release SA. In the free-living or nonpathogenic stage, SghA is not synthesized because of tight control by the negative regulator protein SghR, which binds directly to the promoter of sghA and suppresses its expression (131,142). In contrast, during infection this binding effect is reversed by the accumulated plant disaccharide sucrose, which is stimulated by wounding and microbial infection (25).…”
Section: Switch From Infection To Colonizationmentioning
confidence: 99%